2014
DOI: 10.1007/978-1-4939-1167-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Serotonin Receptors in Nicotine Addiction

Abstract: Regulation of normal or abnormal behaviour is critically controlled by the central serotonergic systems. Recent evidence has suggested that serotonin (5-HT) neurotransmission dysfunction contributes to a variety of pathological conditions, including depression, anxiety, schizophrenia and Parkinson's disorders. There is also a great amount of evidence indicating that 5-HT signalling may affect the reinforcing properties of drugs of abuse by the interaction and modulation of dopamine (DA) function. This chapter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 160 publications
(108 reference statements)
2
12
0
Order By: Relevance
“…Our data on the LHb further support the significant involvement of this small epithalamic area [28,29] and the 5-HT 2A R system [17,35] and their interaction in nicotine effects in the brain and, in general, in drug dependency. Nicotine's modulation is a complex phenomenon and, apart from the rewarding effect mediated by increasing DAergic transmission [7], this alkaloid modulates different neurotransmitter systems.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our data on the LHb further support the significant involvement of this small epithalamic area [28,29] and the 5-HT 2A R system [17,35] and their interaction in nicotine effects in the brain and, in general, in drug dependency. Nicotine's modulation is a complex phenomenon and, apart from the rewarding effect mediated by increasing DAergic transmission [7], this alkaloid modulates different neurotransmitter systems.…”
Section: Discussionsupporting
confidence: 76%
“…Nicotine's modulation is a complex phenomenon and, apart from the rewarding effect mediated by increasing DAergic transmission [7], this alkaloid modulates different neurotransmitter systems. Among them, nicotine affects 5-HT neurons and 5-HT-innervated brain areas [17,36]. For instance, the LHb receives a dense serotonergic innervation from the raphe nuclei [30], expresses several 5-HTR subtypes [30,31], the HT2A gene [37], and 5-HT 2A R protein, both on neurons and glial cells [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On that side, of the less structural similarity, are the results of both nicotine and caffeine. Nevertheless, it has been observed that nicotine exhibits an antistress activity [29,30,31], is causing illusions [32] as well as it causes or it could cause addiction [33], and is widely known that the vast majority of the studied compounds are causing similar effects. When the discussion comes to caffeine, that causes dopamine release in specific regions of the brain [33,34], a matching to cocaine that acts similar in the brain, or due to its calm down effect [35,36,37,38], connection to serotonin and endomorphines could have been observed, as well.…”
Section: Similarities Based On Structural Patternsmentioning
confidence: 99%